A Revised Comparison between Fama and French Five-Factor Model and Three-Factor Model——Based on China’s A-Share Market - Zhang, Zhijing; Yu, Yue; Ma, Qinghua; Yao, Haixiang (Journal of Advances in Applied & Computational Mathematics, 2022)
In allusion to some contradicting results in existing research, this paper selects China’s latest stock data from 2005 to 2020 for empirical analysis. In this paper, the redundant factors (HML, CMA) are orthogonalized, and the regression analysis of the 5*5 portfolio of Size-B/M and Size-Inv is carried out with these two orthogonalized factors. It found that the HML and the CMA are still significant in many portfolios, indicating that they have a strong explanatory ability, which is also consistent with the results of GRS test. All these show that the five-factor model has a better ability to explain the excess return rate. Then, we analyze the possible reasons for the strong explanatory ability of the HML, CMA, and RMW from the aspects of price-to-book ratio, turnover rate, and correlation coefficient. We also explain the results and analyze China’s stock market policy changes and investors’ investment style in recent years.